INCREASED CAPACITY OF THE UNDERSTANDING OF THE CONCEPT AND THE ABILITY TO SOLVE PROBLEMS THROUGH THE IMPLEMENTATION OF THE MODEL OF TEACHING MATHEMATICS REALISTIC BASED ON COGNITIVE CONFLICT STUDENTS - Dewi Herawaty; Rusdi Rusdi (IKIP Siliwangi and I-MES, 2016)
This research aims at: 1) the influence of the implementation of the model of teaching mathematics realistic based on cognitive conflict students to the ability to understanding the concept and troubleshooting capabilities; 2) determine the larger capacity of the understanding of the concept through the implementation of the model of teaching mathematics realistic based on cognitive conflict junior secondary school students the City of Bengkulu. 3) determine the great improvement of the ability to solve problems through the implementation of the model of teaching mathematics realistic based on cognitive conflict SMP students Bengkulu City.To achieve the goal of this research is to apply Research Design pseudo experiments with research design Pretest-Postest Nonequivalent Control Group Design, with the test instrument the ability to understanding the concept and test the troubleshooting capabilities. The data has been analyzed using the test gains. The results of this research is 1) the ability of understanding the concept and troubleshooting class experiment the given learning with PMR is better than with the ability to understanding the concept and troubleshooting control classes assigned to conventional mathematics lesson; 2) increase the ability of the understanding of the concept through the implementation of the model of teaching mathematics based on cognitive conflict SMP students Bengkulu City is significant with the index gain of 0,755 (high-level); 3) increase the ability to solve problems through the implementation of the model of teaching mathematics based on cognitive conflict SMP students Bengkulu City is significant with the index gain of 0,500 level (is).